MINERALOGICAL AND PETROGRAPHIC COMPOSITION OF ORE-BEARING ROCKS IN THE CHOLCHARATOV PROSPECTIVE AREA AND THEIR SIGNIFICANCE IN THE LOCALIZATION OF MINERALIZATION (SOUTH BUKANTOV) - Kholdorov, O.O; Tilovov , F.S.; Berkinov , N.A (ANTIS PUBLISHER, 2024)
Objective: This study investigates the mineralogical and petrographic composition of ore-bearing rocks in the Cholcharatov prospective area (South Bukantov) to elucidate their role in the localization and formation of mineralization. Method: Comprehensive mineralogical and petrographic analyses were conducted on ore-bearing rocks, with a focus on identifying the composition, structure, and mineral associations within the region. Particular attention was given to carbon-containing shales and their interactions with adjacent lithological units, such as quartzites. Results: The primary ore-bearing rocks in the Cholcharatov area were identified as carbon-containing shales, hosting significant sulfide mineralization. The mineralization predominantly occurs within the carbonaceous shales and is intensified in zones of contact with quartzites. These findings highlight the critical role of lithological and structural controls in localizing ore deposits. Novelty: This study provides new insights into the mineralogical and petrographic characteristics of the Cholcharatov area, emphasizing the significance of carbonaceous shales in hosting sulfide mineralization. The research contributes to the broader understanding of ore deposit formation mechanisms and offers a refined model for targeting mineralization in similar geological settings.